Pharmacological Inhibition of Toll-Like Receptor-4 Signaling by TAK242 Prevents and Induces Regression of Experimental Organ Fibrosis - Bhattacharyya, Swati; Wang, Wenxia; Tamaki, Zenshiro; Shi, Bo; Yeldandi, Anjana; Tsukimi, Yasuhiro; Yamasaki, Masashi; Varga, John (Frontiers in Immunology, 2018)
Systemic sclerosis (SSc) is a poorly understood heterogeneous condition with progressive multi-organ fibrosis. Recent genetic and genomic evidence suggest a pathogenic role for dysregulated innate immunity and toll-like receptor (TLR) activity in SSc. Levels of both TLR4, as well as certain endogenous TLR ligands, are elevated in skin and lung tissues from patients with SSc and correlate with clinical disease parameters. Conversely, genetic targeting of TLR4 or its endogenous “damage-associated” ligands ameliorates progressive tissue fibrosis. Targeting TLR4 signaling therefore represents a pharmacological strategy to prevent intractable fibrosis. We examined the effect of TAK242, a small molecule TLR4 inhibitor, in preclinical fibrosis models and in SSc fibroblasts. TAK242 treatment prevented, promoted regression of, bleomycin-induced dermal and pulmonary fibrosis, and reduced the expression of several pro-fibrotic mediators. Furthermore, TAK242 ameliorated peritoneal fibrosis and reduced spontaneous hypodermal thickness in TSK/+ mice. Importantly, TAK242 abrogated collagen synthesis and myofibroblasts differentiation in explanted constitutively active SSc fibroblast. Altogether, these findings identify TAK242 as an anti-fibrotic agent in preclinical models of organ fibrosis. TAK242 might potentially represent a novel strategy for the treatment of SSc and other fibrotic diseases.